Possible case of trichinellosis associated with beaver (Castor fiber) meat. Issue 3 (3rd May 2018) - Bronstein, A.M.; Lukashev, A.N.
Abstract: Although there have been occasional reports of rare and low-level trichinellae infestation in beavers, no human cases of beaver-associated trichinellosis have been described. This report presents a possible case of human trichinellosis linked to beaver meat. Increasing consumption of beaver meat necessitates raising awareness of this potential source of trichinellosis.